Alfa Galactosidos y fitatos en semillas germinadas de Phaseolus vulgaris y de Vigna sinensis - Sangronis, E.=700 1 Torres, A.; Sanabria, N.
(En, Es)
ilus., 9 ref.
Keywords: PHASEOLUS VULGARIS; VIGNA UNGUICULATA UNGUICULATA; GERMINACION; INOSITOL; FOSFATOS; ALFA GALACTOSIDOS; SEMILLAS; VENEZUELA; AGRONOMIA TROPICAL